Study of the Effects of Various Polyphenols on Proliferative Processes and the Functional State of Liver Mitochondria of Experimental Toxic Hepatitis - Dalimova, Surayyo; Mukhammadjonova, Guzal; Umarova, Gulbakhor; Kuziev, Sherali; Tukhtaev, Davron; Yunusova, Muslima; Khamdamova, Nigora; Khamraev, Sobir; Gafurov, Mahmudjon; Khasanov, Feruzbek; Eshboev, Farkhod (Asian Journal of Biological and Life Sciences)
Background: Toxic hepatitis is considered one of the most serious concern of health care. Because, would be reason for developing liver cirrhosis and primary liver cancer. Materials and Methods: In this work, models of toxic hepatitis animals prepared and effects of various polyphenols on the liver mitochondria of the model animals were studied. For this, liver mitochondria of the animals were isolated and the lipid peroxidation, the respiration rate and parameters of oxidative phosphorylation, activity of enzymes of the respiratory chain, and mitochondrial proteins synthesis were determined. Results: It was defined that studied polyphenols of plant origin, which are rutan and hetasan showed antioxidative properties. It was shown that these polyphenols express stabilization influence on decreased functional conditions of liver mitochondria in the case of toxic hepatitis by stimulating energy-producing function, activity of oxidative chain enzymes and mitochondria proteins synthesis. During the investigations of polyphenols’ antiproliferative abilities, it was defined that rutan is characterized by considerable antifibrotic activity. Conclusion: The plant polyphenols rutan and hetasan are hepatoprotectors with pronounced therapeutic effects in toxic hepatitis. In this study, it was determined that the therapeutic effect of these polyphenols includes an improvement of energy metabolism, a decrease of the process of lipid peroxidation of mitochondrial membranes, as well as the proliferation of fibrous tissue in the liver parenchyma. It may be occurs do to antioxidant activity of the polyphenols.
Keywords: Functional state; Polyphenols; Proliferative processes; Toxic hepatitis.